STRATEGI PENDIDIKAN KARAKTER PADA DAYAH SALAFI DI ACEH - Saiful Saiful (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2015)
One of advantage the Salafi Islamic boarding school education system is the success instills character education to the students in all aspects of life, so it could produce graduates who have the idealism, intellectual ability and behavior of noble (al-akhlaq al-karimah). The aim of this study is to determine the educational strategy in dayah salafi character, thus giving to graduates who have a high ta'zhim to teungku/ulama, to determine the steps to be taken teungku dayah salafi character education students, to determine the form of social interaction teungku and students at dayah salafi, to determine the role teungku dayah salafi clerics in character education students and to determine the success factors and barriers to dayah salafi character education. This discussion uses descriptive qualitative research method with a phenomenological approach, historical, and sociological. Data collection techniques are observation, interviews, and have documentation. The sample in this study is five (5) dayah salafi namely; Dayah Darussalam Labuhan Haji Aceh Selatan, Dayah Bustanul Huda Aceh Timur, Dayah Mudi Mesra Samalanga Aceh Utara, Dayah Tgk. Chik Tanoh Abee Seulimun Aceh Besar, and Huda Islamic boarding school Thalibul Huda Bayu Lampeuneurut Aceh Besar. Results of the study are: Strategy on dayah salafi character education in Aceh, as follows: (1) Moral Knowing. (a) Knowledge development of character. (b) Development  of tafaqquh fi al-din.  (2) Moral Feeling  (a). The concept of sincerity, (b) Preservation of the value of culture dayah, (c) Modeling, (d) discipline, (e) Prioritize concepts of simplicity, (f) Application of education without violence. (3) Moral action. (a) Education is directed to the practice.      (2)  Habituation,  Step-by-step application of character education in Dayah Salafi, namely:     (1) Internalization of morality in teaching, (2) Strengthening the morality of students,       (3) Application morality in life, (4) Evaluation continuously, (5) Designing environment dayah conducive , Role teungku in character education in dayah salafi namely:                 (1) Teachers and counselors, (2) Assist and justice to students, (3) Tengku role as parents of students, (4) integration of character education, (5) Cooperation with parents of students and the community, (6) Improving education management dayah. Success factors and obstacles in dayah salafi character education, namely: (1) success factors: Compliance students, their values and culture dayah, responsibilities of parents of students, and community support. (2) inhibiting factors: Differences in the character of the students and the difference in residence.